On critical pounding mechanism of base-isolated buildings using an optimized multi-hazard method - Ali Majdi; Ataallah Sadeghi-Movahhed; Denise-Penelope N. Kontoni; Nashwan Adnan Othman; Muhannad Riyadh Alasiri; Saiful Islam; Majid Movahedi Rad (Results in Engineering)
In many studies on the effect of pounding on isolated structures, the failure to consider all potential pounding scenarios, including floor-to-floor (FF), floor-to-column (FC), and pounding with a moat wall, can introduce uncertainty into the obtained results. Therefore, this study investigates the critical pounding scenarios in isolated structures subjected to seismic excitations. Three primary types of pounding are examined: FF, FC, and MW, under both two-sided and one-sided limitations. Additionally, the study investigates the effects of varying gap sizes and structural heights on the response of structures subjected to each pounding type. In the FF and FC scenarios, six-story and nine-story base-isolated buildings are analyzed in relation to adjacent six-story fixed-base structures. The endurance time method is employed to obtain the seismic responses of the structures. The results indicate that FC pounding consistently induced the highest shear forces in the columns and represented the most critical failure mode. The base-isolated structures that are significantly taller than adjacent fixed-base structures (e.g. 9.6 m) are more susceptible to damage compared to those with similar heights to their neighbors. Furthermore, increasing the gap size can lead to a 100 % rise in inter-story drift under two-sided FF pounding and a 126 % increase in column shear force under two-sided FC pounding.